THz based non-destructive testing system for Security and Inspection Applications - Sobczyk, Artur; Sypek, Maciej; Ducin, Izabela; Wiśniewski, Piotr; Kowalczyk, Adam (Photonics Letters of Poland, 2024)
Terahertz (THz) technology has garnered significant attention in non-invasive inspection and security applications due to its ability to penetrate common materials like paper, plastics, and fabrics while remaining non-ionizing. This study presents a package THz scanner utilizing a commercially available 292 GHz wave IMPATT source and a custom-designed 3D-printed multifunctional diffractive optical component for beam shaping. The novelty lies in application of the THz source with limited coherence and broadband detectors line. Thus, coherent noise can be suppressed. We discuss the system's design, construction, and performance, demonstrating its feasibility as a cost-effective and adaptable solution for package inspection. Full Text: PDF References P. Zientek, Maszyny Elektryczne-Zeszyty Problemowe 3/2016 (2016) DirectLink W. Nsengiyumva, S. Zhong, L. Zheng, W. Liang, B. Wang, Y. Huang, X. Chen,Y. Shen, "Sensing and Nondestructive Testing Applications of Terahertz Spectroscopy and Imaging Systems: State-of-the-Art and State-of-the-Practice", IEEE Transactions on Instrumentation and Measurement 72 (2023) CrossRef J. Suszek, A. Semion, M. Bieda, N. Błocki, D. Coquillat, G. Cywiński, E. Czerwińska, M. Doch, A. Kowalczyk, N. Pałka, A. Sobczyk, P. Zagrajek, M. Zaremba, A. Kołodziejczyk, W. Knap, M. Sypek, "3-D-Printed Flat Optics for THz Linear Scanners", IEEE Transactions on Terahertz Science and Technology 5, 2 (2015) CrossRef J. Sun, F. Hu, "Three-dimensional printing technologies for terahertz applications: A review", Int. J. RF. Microw. Comput. Aided Eng. 30, 1 (2019) CrossRef A. Siemion, M. Surma, P. Komorowski, I. Ducin, P. Sobotka, "Terahertz diffractive optics: different way of thinking", SPIE Proceedings: Terahertz Emitters, Receivers, and Applications 11499 (2020) CrossRef A. Sobczyk, K. Filak-Mędoń, A. Kowalczyk, J. Suszek, M. Zdrojek, and M. Sypek, "Ultra-low reflection of sub-THz waves in graphene-based composite with metasurface for stealth technology", Opt. Express 32, 32118-32127 (2024). CrossRef